2020
DOI: 10.1039/d0bm00650e
|View full text |Cite
|
Sign up to set email alerts
|

Surface grafting of Fc-binding peptides as a simple platform to immobilize and identify antibodies that selectively capture circulating endothelial progenitor cells

Abstract: Antibody surface immobilization via Fc-binding peptides is a promising strategy to capture circulating cells such as endothelial progenitor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…We have recently shown that antibodies immobilized through surface-grafted RRGW peptides designed to interact with the Fc region of IgG2a antibodies can selectively capture ECFCs from a mixture of cells under dynamic flow conditions [ 23 ]. A major obstacle hampering the use of protein G on implanted biomaterials such as stents is its unknown immunogenic profile and the possibility that it can provoke undesirable host immune responses [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently shown that antibodies immobilized through surface-grafted RRGW peptides designed to interact with the Fc region of IgG2a antibodies can selectively capture ECFCs from a mixture of cells under dynamic flow conditions [ 23 ]. A major obstacle hampering the use of protein G on implanted biomaterials such as stents is its unknown immunogenic profile and the possibility that it can provoke undesirable host immune responses [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, improved bio-affinity-based antibody immobilization techniques emerged as an alternative that can enhance the potential of next-generation ECFC-capture stents [22][23][24]. Li et al demonstrated that stent surfaces modified with anti-CD34 antibodies immobilized via the Fc-binding protein A improved in vivo stent endothelialization compared to unmodified controls [25].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that antibodies immobilized through the Fc region by surface conjugated RRGW can selectively capture ECFCs from a mixture of cells under dynamic flow conditions 20 . A major obstacle hampering the use of protein G on implanted biomaterials such as stents is its unknown immunogenic profile and the possibility that it can provoke undesirable host immune responses 37 .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, improved bio-affinity-based antibody immobilization techniques emerged as an alternative that can enhance the potential of a new generation of ECFC-capturing stents [19][20][21] . Li et al…”
Section: Introductionmentioning
confidence: 99%
“…More biomarkers of EPCs have emerged in this research field, touching upon CD34, 345 CD133, 346 vascular endothelial-cadherin (VE-cadherin), 347 CD146, 344 endoglin, 348 vascular endothelial growth factor type 2 receptor (VEGFR2), 328 CD144, and CD309. 349 Fixation of antibody for bounding these biomarkers onto materials could potently attract these cells to pathological sites. Antibody fragments scFv, single chain fragment variable binding to VEGFR2 can be utilized to guide attachment and multiplying of VEGFR2-positive cells covering circulating ECs and EPCs.…”
Section: Strategies Of Lesion-localizing Delivery For Treating Athero...mentioning
confidence: 99%